Detection of Dengue Virus Nonstructural Protein 1 (NS1) by Using ELISA as a Useful Laboratory Diagnostic Method for Dengue Virus Infection of International Travelers. Issue 3 (8th March 2013) - Moi, Meng Ling; Omatsu, Tsutomu; Tajima, Shigeru; Lim, Chang‐Kweng; Kotaki, Akira; Ikeda, Makiko; Harada, Fumiue; Ito, Mikako; Saijo, Masayuki; Kurane, Ichiro; Takasaki, Tomohiko
Abstract Background Dengue virus ( DENV) nonstructural protein 1 ( NS1) has been used as a novel diagnostic marker during the early phase of DENV infection. Methods Presence of NS1 antigen was examined using 336 serum samples obtained from 276 travelers returning to Japan from Asia, Central and South America, Pacific Islands, and Africa with dengue. Assay specificity was evaluated using 148 non‐dengue samples. Results Positive rates among four DENV serotypes were 68%–89%. NS1 antigen positive rates were at similar levels between primary infection and secondary infection. NS1 antigen positive rates were 88%–96% on days 1–5, 75%–100% on days 6–10, and 36–60% on ≥day 11. Positive rates using real‐time polymerase chain reaction (RT‐PCR) were over 70% on days 1–5, but decreased thereafter. Conclusions The results indicate that NS1 antigen positive rates were higher than those of RT‐PCR during longer period of early phase in DENV infection. Thus, NS1 antigen ELISA is a useful tool for confirming DENV infection in international travelers, when it is used in combination with anti‐DENV IgM ELISA.